2014
DOI: 10.1002/dc.23103
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic renal cell carcinoma, clear cell type, of the parotid gland

Abstract: Renal cell carcinoma (RCC), clear cell type, is a commonly encountered metastatic tumor that can present at unusual anatomic sites many years after the primary tumor resection. Noncutaneous metastasis to the parotid gland is unusual; however, a number of cases of parotid RCC metastasis have been reported. Fine-needle aspiration biopsy (FNAB) is regularly utilized during the evaluation of salivary gland lesions, where it has a high sensitivity, specificity, and accuracy; however, the identification and definiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 34 publications
(54 reference statements)
1
12
1
Order By: Relevance
“…Classically, RCC presents positive immunohistochemical staining for vimentin and cytokeratin, and negative staining for CK-7 and CK-20. All of these markers were present in this case report 5 .…”
Section: /6supporting
confidence: 56%
See 1 more Smart Citation
“…Classically, RCC presents positive immunohistochemical staining for vimentin and cytokeratin, and negative staining for CK-7 and CK-20. All of these markers were present in this case report 5 .…”
Section: /6supporting
confidence: 56%
“…Metastasis occurs in only 1-4% of all salivary gland tumors, and the parotid is the most affected 4 . Approximately 0.1% of all salivary gland metastatic neoplasms originate from renal malignancies 5 . Parotid neoplasm is diagnosed from a thorough clinical history and physical examination of the patient.…”
mentioning
confidence: 99%
“…Our research strategy revealed a total of 83 relevant papers published from 1965-2022 (a few references). [ 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 ] A total of 100 patients included 55 males and 35 females with a male to female ratio of 1.6:1. The maximum number of cases were from the USA ( n = 17) followed by Poland ( n = 11), Turkey = UK ( n = 10), and Japan = Italy ( n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…The first cases of parotid involvement due to RCC metastases were reported by Patey et al in 1965 7 . Since then, there have been limited reported cases of this phenomenon 6,[8][9][10][11][12][13][14][15][16] . In their review of the literature, Lawlor et al reported 45 cases of RCC metastasizing to the parotid, of which only 31 were complete case presentations 6 .…”
Section: Discussionmentioning
confidence: 99%